The High-Temperature Synthesis of the Nanoscaled White-Light Phosphors Applied in the White-Light LEDs - Hao-Ying Lu; Meng-Han Tsai (Advances in Materials Science and Engineering)
The white-light phosphors consisting of Dy3+ doped YPO4 and Dy3+ doped YP1-XVXO4 were prepared by the chemical coprecipitation method. After the 1200°C thermal treatment in the air atmosphere, the white-light phosphors with particle sizes around 90 nm can be obtained. In order to reduce the average particle size of phosphors, the alkaline washing method was applied to the original synthesis process, which reduces the particle sizes to 65 nm. From the PLE spectra, four absorption peaks locating at 325, 352, 366, and 390 nm can be observed in the YPO4-based phosphors. These peaks appear due to the following electron transitions: 6H15/2→4K15/2, 6H15/2→4M15/2+6P7/2, 6H15/2→4I11/2, and 6H15/2→4M19/2. Besides, the emission peaks of wavelengths 484 nm and 576 nm can be observed in the PL spectra. In order to obtain the white-light phosphors, the vanadium ions were applied to substitute the phosphorus ions to compose the YP1-XVXO4 phosphors. From the PL spectra, the strongest PL intensity can be obtained with 30% vanadium ions. As the concentration of vanadium ions increases to 40%, the phosphors with the CIE coordinates locating at the white-light area can be obtained.